Analisis Persepsi Pengguna Jalan Terhadap Fasilitas Penyeberangan di Ruas Jalan AP.Pettarani - Oktavianty Batto; Rais Rachman; Monika D.M Palinggi (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
Pedestrian Bridge is a pedestrian facility that is very useful for smooth traffic. Meanwhile, from the observations, the Pedestrian Bridge on Jalan A.P. Pettarani has not been used optimally, for example, pedestrians still use the road as a medium for crossing. This study aims to determine the characteristics of pedestrians and the perceptions of pedestrians towards the Pedestrian Bridge facility on Jalan A.P. Pettarani. The method used is the interview method using a questionnaire or questionnaire and analyzed by descriptive analysis method. Based on the results of the study, it was found that the characteristics of pedestrians were more dominated by men with an age range of 17-26 years by students, and the perceptions of pedestrians varied greatly, both those who used and did not use the A.P Pettarani Pedestrian Bridge. Of all the variables studied, the variable that influenced the most was the variable X3, namely the distance traveled in which in some cases pedestrians were reluctant to use the Pedestrian Bridge because the distance from the point of traveling to the destination was further away. So that sometimes many pedestrians prefer to cross the road.